2020
DOI: 10.3390/microorganisms8030318
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides Decrease Bacterial Diversity and Abundance of Irrigated Rice Fields

Abstract: Bacteria play an important role in soil ecosystems and their activities are crucial in nutrient composition and recycling. Pesticides are extensively used in agriculture to control pests and improve yield. However, increased use of pesticides on agricultural lands results in soil contamination, which could have adverse effect on its bacterial communities. Here, we investigated the effect of pesticides commonly used on irrigated rice fields on bacterial abundance and diversity. Irrigated soil samples collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 55 publications
(63 reference statements)
0
17
0
1
Order By: Relevance
“…Human activities are closely related to pollutants, drugs, chemicals, and antibiotics, which has disturbed the microbiota of the environment and organisms ( 7 ). For instance, the increased Lysinibacillus was highly resistant to heavy metal pollution in farmland systems ( 20 ), and the abundance of Acinetobacter rises in pesticide-exposed areas ( 21 ). Another co-occurring genus, Comamonas , has also been confirmed to be highly correlated with sulfur metabolism, nitrogen metabolism, and the TCA cycle ( 22 ), in accordance with functional predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Human activities are closely related to pollutants, drugs, chemicals, and antibiotics, which has disturbed the microbiota of the environment and organisms ( 7 ). For instance, the increased Lysinibacillus was highly resistant to heavy metal pollution in farmland systems ( 20 ), and the abundance of Acinetobacter rises in pesticide-exposed areas ( 21 ). Another co-occurring genus, Comamonas , has also been confirmed to be highly correlated with sulfur metabolism, nitrogen metabolism, and the TCA cycle ( 22 ), in accordance with functional predictions.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of different pesticides has been assessed by evaluating changes in gene expression and biochemical enzymatic activities and in the diversity and composition of soil bacterial communities (Feld et al ., 2015; Bacmaga et al ., 2018; Storck et al ., 2018; Bacmaga et al ., 2019). A recent study has shown that pesticides decrease the bacterial diversity and abundance in irrigated paddies (Onwona‐Kwakye et al ., 2020). Bioactivity, richness and microbial diversity also decrease when the concentration of heavy metals increase (Yin et al ., 2015; Xie et al ., 2016; Feng et al ., 2018; Liu et al ., 2018; Luo et al ., 2018; Fatimawali et al ., 2020; Thomas IV et al ., 2020; Zhao et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Chemical pesticides and heavy metals played a vital role in sustaining crops and livestock yield for several decades and have negative influence on environment ( Duke, 2018 ; Onwona-Kwakye et al., 2020 ). Irrigation of agricultural soils with wastewater have high risk of accumulation of persistent organic and inorganic pollutants in soil.…”
Section: Introductionmentioning
confidence: 99%